Measuring Financial Development in Sub-Saharan Africa - Gelbard, Enrique (IMF Working Papers; Working Paper ;, 1999)
This study introduces an index for measuring financial development and a set of six indices representing key characteristics of the financial systems in 38 sub-Saharan African countries. The results show that these countries have made good progress in improving and modernizing their financial systems during the last decade, particularly with regard to financial liberalization and the adoption of indirect instruments of monetary policy. In many countries, however, the range of financial products remains extremely limited, interest rate spreads are wide, capital adequacy ratios are insufficient, judicial loan recovery is a problem, and the share of nonperforming loans is large.